A review of the current state of knowledge on gold mineralisation in Benin Republic, West Africa. Issue 1 (2nd January 2019) - Adjo, Fatchessin Bruno; Bolarinwa, Anthony Temidayo; Adissin Glodji, Luc; Dongmo, Franck Wilfried Nguimatsia; Olajide-Kayode, Jerry Olugbenga
ABSTRACT: Gold in Benin occurs as primary and alluvial forms in various deposits and occurrences. The mineralisation has a regional distribution covering, in particular, the Atacora area (Natitingou) and the regions of Bembèrèkè, Djougou and Dunkassa which are between the 9th and 11th parallel north. The data collected during previous work allow us to recognise the main style of primary gold as being quartz-vein hosted. This style occurs principally in quartzite, mica schist, schist and amphibolite lithologies, outcropping in the criss-crossing of the faults and the rugged relief. The mineralised veins are milky, deformed and gold is associated with sulphides and tourmaline. In these veins, gold exhibits three forms: free native metal, tellurides, and combined or included in sulphides. These gold-bearing quartz veins would proceed from hydrothermal solutions related to granitic mass. Classical characteristics available about the primary gold mineralisation in Bénin are inadequate to better clarify its geodynamic context. However, it has some similarities with deposits of the Precambrian terranes in adjacent countries (Pourra deposit in Burkina Faso and Kalana deposit in Mali) which are characterised by epigenetic gold deposits in Precambrian metamorphic terranes. Also, the vein gold of Bénin are mostly located in Precambrian metamorphosed sedimentary and volcanic formations ; these could also have the epigenetic disseminated gold style like in some West African deposits (Ashanti deposit).